Membrane topology modulates β-galactosidase activity against soluble substrates - Sanchez, Julieta Maria (2002)
The effect of bio-surfaces of contrasting curvature, on the kinetic parameters of ortho-nitrophenyl-β-D-galactopiranoside hydrolysis catalyzed by E. coli β-galactosidase, was investigated. The self-aggregating state and structure of the amphiphiles (Phosphatidylcholine, Lubrol-PX, Triton X-100, DocNa, SDS and CTAB) were inferred from their c.m.c. values and light-scattering measurements. Low curvature phosphatidylcholine or mixed phosphatidylcholine-detergent vesicles increased V max without affecting K M. High curvature micellar structures containing ionic detergents modulated negatively the enzyme activity (decreased or abolished V max and increased K M). Neither micelles containing non-ionic detergents nor the amphiphiles in a monomeric form, affected enzyme activity. CTAB at a concentration bellow its c.m.c but incorporated into a bilayer, became an activator (K M decreased respect to the control). Non-enzymatic interfacial hydrolysis of the substrate was discarded. Enzyme-membrane interaction and membrane elasticity, were evaluated using monomolecular layers at the air-water interface. Beyond particular molecular structures, topology affected the direction of the modulatory effects exerted by these amphiphiles on β-galactosidase activity. © 2002 Elsevier Science B.V. All rights reserved.